The Effect of Working Capital Management, Operational Efficiency, and Profitability on Financial Sustainability of SMEs - Rahmiyati, Nekky; Wahidhani, Eha Hasni; Fitrianingsih, Dwi; Rachmawati, Titiek (IJBLE Scientific Publications Community Inc., 2024)
This study examines the effects of working capital management (WCM), operational efficiency (OE), and profitability on the financial sustainability (FS) of small and medium-sized enterprises (SMEs). Utilizing quantitative analysis and data collected from a diverse sample of SMEs, the research highlights the significant relationships between these variables. The results indicate that effective WCM and enhanced OE positively influence profitability, which, in turn, plays a crucial mediating role in promoting financial sustainability. This study contributes to the existing literature by demonstrating how integrated management strategies that prioritize working capital practices and operational improvements can enhance the financial health of SMEs. The findings provide practical implications for SME owners and managers, suggesting that a focus on these critical factors is essential for achieving long-term financial viability. Future research directions are proposed to explore sector-specific impacts and longitudinal effects on financial sustainability.